The Visit - Kornetzky, Brigitte Uttar (Switzerland : Magpie Dream Pictures, 2007)
“The Visit” delves deep into Sierra Leone to celebrate the calmness and good spirit of its people after the civil war. Six years after signing the peace treaty, however, conditions remain difficult. The filmmaker explores the kaleidoscopic story of Sierra Leona, talks to survivors trying to understand how they cope with the leftovers of the bloody war and what their hopes for the future are.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films